Delight training in practice scenarios: sizing of curricular internships vacancies at the Health Department of the state of Mato Grosso (Research, Society and Development, 2023)
This article aims to describe the process of collective construction of the methodology of sizing curricular internships vacancies conducted by the School of Public Health for the scenarios of health services practices of the Mato Grosso State Department of Health considering the diversity of knowledge, the importance of complementarity of training and practices of health services. This is an experience report that occurred with the participation of the authors, managers and workers between October 2021 and September 2022, through virtual workshops involving 176 participants with the objective of elaborating and validating the methodology. Indicators and parameters were selected to represent the diagnosis of direct or indirect care services, consisting of hospitals, deconcentrated areas, superintendences and regional offices. The variables used to elaborate the calculation formulas were the number of beds, the rate of hospital occupancy and the number of workers in each service. The elaboration of this tool made it possible to highlight creativity, criticality, plurality of knowledge, collective construction from empirical and scientific knowledge, resulting in a singular and innovative method for the Unified Health System of Mato Grosso.  Considering the scarcity of national and international productions and the novelty of the developed method, it is intended that the report of this experience produces concerns and interest of new publications, allowing expansion and qualification of the theme addressed for the strengthening of public policies of Teaching Service.